Dietary restriction and insulin‐like signalling pathways as adaptive plasticity: A synthesis and re‐evaluation. (21st August 2019) - Regan, Jennifer C.; Froy, Hannah; Walling, Craig A.; Moatt, Joshua P.; Nussey, Daniel H.
Abstract: Dietary restriction (DR) under laboratory conditions generally extends life span and delays ageing across species as diverse as yeast, nematode worms, flies and mice, and is underpinned by taxonomically conserved physiological pathways, notably the insulin‐like signalling pathway (IIS). Despite growing excitement about the links between DR/IIS and ageing within biogerontology, our understanding of why the DR response and associated pathways evolved under natural selection remains controversial and limited. Here, we provide a brief overview of current understanding of the relationship between DR and IIS and ageing from modern biogerontology and go on to summarize the evidence that the IIS pathway integrates a range of important environmental cues including photoperiod, temperature and humidity, as well as nutrition. We go on to discuss the main existing evolutionary explanations for DR and argue that they are not mutually exclusive and are too nutrition‐focussed to fully explain the evolutionary origin of the IIS pathway. In the wild, environmental cues and pressures are dynamic and multivariate, and physiological pathways capable of integrating multiple predictive cues could be strongly favoured by natural selection. We hypothesize that the IIS and related pathways, such as mTOR, evolved to detect and integrate a wide range of environmental cues (not just diet) that are predictive of important selective pressures in the wild. Available evidence suggests the pathway is capable of triggering a range of phenotypic responses, depending on the cues provided, ranging from profound physiological remodelling (e.g. diapause, aestivation, hibernation) associated with promoting survival through challenging environments, to more subtle responses to acute, fine‐scale variation in the environment which may allow individuals to better match their level of reproductive investment to their conditions. We argue that the IIS pathway underpins important adaptive phenotypic plastic responses to a wide range of environmental inputs, of which diet is just one. A multi‐disciplinary approach combining perspectives and methods from biogerontology, cell biology, ecology and evolutionary biology will be essential to develop our understanding of the evolutionary origins of this pathway and the way natural selection and the environment have shaped variation in the IIS pathway's response to different environmental cues. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.